Fetal Growth Restriction Alters Cerebellar Development in Fetal and Neonatal Sheep - Yawno, Tamara; Sutherland, Amy E.; Pham, Yen; Castillo-Melendez, Margie; Jenkin, Graham; Miller, Suzanne L. (Frontiers in Physiology, 2019)
Fetal growth restriction (FGR) complicates 5-10% of pregnancies and is associated with increased risks of perinatal morbidity and mortality. The development of cerebellar neuropathology in utero, in response to chronic fetal hypoxia, and over the period of high risk for preterm birth, has not been previously studied. Therefore, the objective of this study was to examine the effects of FGR induced by placental insufficiency on cerebellar development at three time points in ovine fetal and neonatal development: i) 115 days gestational age (d GA), ii) 124 d GA and iii) 1 day old postnatal age. We induced FGR via single umbilical artery ligation at 105 d GA in fetal sheep, term is 147 d GA. Animals were sacrificed at 115 d GA, 124 d GA and 1 day old postnatal age, fetuses and lambs were weighed and the cerebellum collected for histopathology. FGR lambs demonstrated neuropathology within the cerebellum after birth, with a significant, 18% decrease in the number of granule cell bodies (NeuN+ immunoreactivity) within the internal granular layer (IGL) and an 80% reduction in neuronal extension and branching (MAP+ immunoreactivity) within the molecular layer (ML). Oxidative stress (8-OHdG+ immunoreactivity) was significantly higher in FGR lambs within the ML and the white matter compared to control lambs. The structural integrity of neurons was already aberrant in the FGR cerebellum at 115 d GA, and by 124 d GA inflammatory cells (Iba-1+ immunoreactivity) were significantly upregulated and the blood brain barrier was compromised (Pearls, albumin and GFAP+ immunoreactivity). We confirm that cerebellar injuries develop antenatally in FGR, and therefore interventions to prevent long-term motor and coordination deficits should be implemented either antenatally and/or perinatally, targeting neuroinflammatory and oxidative stress pathways.